The Effect of Prenatal Yoga on the Incidence of Constipation on the Discomfort of Pregnant Women - Fresthy Astrika Yunita; Hardiningsih Hardiningsih (Indonesian Journal of Global Health Research, 2026)
During pregnancy, significant physiological changes occur that can cause discomfort in pregnant women. One of the discomforts experienced by pregnant women is the occurrence of constipation. Constipation in pregnant women is caused by an increase in progesterone production which causes a decrease in smooth muscle tone, including in the digestive system, resulting in a slowdown of the digestive system. Prenatal yoga can be one of the alternative non-pharmacological therapies to reduce such discomfort. Objective to determine the effect of prenatal yoga on the incidence of constipation on the discomfort of pregnant women. Pre-experiment with a pre-post test control group design research. The number of samples used was 30 people.  The sampling technique used purposive sampling, with the inclusion criteria of pregnant women in the second trimester who were willing to participate in all stages of the study and had no contraindications to do prenatal yoga. The experimental group will follow a prenatal yoga session conducted for 6 weeks. Constipation measurement was carried out using a Constipation Scoring System (CSS) questionnaire. Data analysis used the Paired t-test statistical test. After the yoga intervention there was a decrease in the average score of constipation (4.1 vs 3.6), the maximum value of constipation is now only 6 from the previous 8.  Respondents who experienced moderate constipation were also reduced quite drastically, namely only 5 people (16.67%) remained and this difference was statistically significant (p value 0.002< 0.05). Prenatal yoga can overcome constipation in pregnant women.